Gas cooling of test masses for future gravitational-wave observatories. (17th August 2021) - Reinhardt, Christoph; Franke, Alexander; Schaffran, Jörn; Schnabel, Roman; Lindner, Axel
Abstract: Recent observations made with advanced LIGO and advanced Virgo have initiated the era of gravitational-wave astronomy. The number of events detected by these '2nd generation' (2G) ground-based observatories is partially limited by noise arising from temperature-induced position fluctuations of the test mass (TM) mirror surfaces used for probing spacetime dynamics. The design of next-generation gravitational-wave observatories addresses this limitation by using cryogenically cooled test masses; current approaches for continuously removing heat (resulting from absorbed laser light) rely on heat extraction via black-body radiation or conduction through suspension fibres. As a complementing approach for extracting heat during observational runs, we investigate cooling via helium gas impinging on the TM in free molecular flow. We establish a relation between cooling power and corresponding displacement noise, based on analytical models, which we compare to numerical simulations. Applying this theoretical framework with regard to the conceptual design of the Einstein telescope (ET), we find a cooling power of 10 mW at 18 K for a gas pressure that exceeds the ET design strain noise goal by at most a factor of ∼3 in the signal frequency band from 3 to 11 Hz. A cooling power of 100 mW at 18 K corresponds to a gas pressure that exceeds the ET design strain noise goal by at most a factor of ∼11 in the band from 1 to 28 Hz.